INTERNET COMMUNICATION IN PROFESSIONAL AVIATION COMMUNITIES - M. A. Melnikova (Научный вестник МГТУ ГА, 2016)
Communication aspects and features of co-operation are examined in professional aviation associations in Internet space. Definition of professional association is Given, its descriptions are distinguished. Advantages of network co-operation of the members of a professional association are exposed. The criteria of classification of types of aviation associations are defined in the internet; the specific character of communication of members the of associations is described on subjects, language forms, video row. The conclusion is reasonable that researches of professional internet-communications in the associations of air specialists will allow to promote efficiency of work of all the industry, and also to influence qualitatively on the image of domestic civil aviation in the eyes of the public.